STUDY FOR ESTIMATION OF AIR-SEA C02 GAS TRANSFER BY WAVE BREAKING MODEL USING SATELLITE DATA — ESTIMATION OF THE FRICTION VELOCITY CONSIDERING WAVE EFFECT - NAOYA SUZUKI; NAOTO EBUCHI; CHAOFANG ZHAO; TAKAHIRO OSAWA; TAKASHI MORIYAMA (International Journal of Remote Sensing and Earth Sciences, 2004)
The determination of wind friction velocity from satellite-derived wind data will take an important role of key factors for computation of C02 flux transfer. It is necessary for relation between wind speed and wind friction velocity to determine that of relation between nondimensional roughness length and wave age, included with all parameters (wind, wave). In this study, we proposed a new method to estimate u„, which is based on the new relationship between non-dimensional roughness and wave velocity, after considering fetch andwave directionality. Consequently, we obtained the new relationship between friction velocity and wind speed. Using this relationship, we estimated the wave frequency from two methods:3 per 2 powers law (Toba, 1972) and WAM model (WAMDI, 1988). The results arc compared with the results estimated from Charnock formula (1955) and the above influence of wave effects on the wind stress is also discussed. A new relationship was established to determine CO. exchange coefficient based on whitecap model (Monahan and Spillane 1984), using U|0-u, relationship in North Pacific Ocean, satellite data of NOAA-AVHRR (SST) and DMSP-SSM-I (wind speed) in Oct., Nov., and Dec. 1991. The C02 exchange coefficient estimated by other models (Wanninkhof, 1992; Liss and Merlivat, 1986; Tans et al., 1990) are also compared with these results. The results show the importance of wave breaking effect.